(untitled) (Mongolian Journal of International Affairs, 2026)
As cultural institutions, museums serve as vital vehicles for international cultural exchange, allowing the general public to understand a nation’s culture and history. In recent years, museums have begun to exert increasingly significant cultural influence on the global stage and play an indispensable role in building national soft power. The concept of museum diplomacy has gradually emerged as a focal point within academic circles; this relatively new subfield of international relations reflects the growing recognition of culture as a strategic resource. This paper aims to analyze the role of museum diplomacy in shaping national soft power, exploring how museums promote mutual understanding and exchange between nations through international cooperation and practice. Using China and the United States as case studies, it elucidates the practical pathways and insights of museum diplomacy in enhancing national image and expanding cultural influence, supplemented by a brief analysis of Mongolia’s potential for development